Social Independent Oil Palm Smallholder Credit Settlement - Sarinda, Maria Elsanda Riva; Eva Dolorosa; Imelda (Faculty of Agriculture Udayana University, 2026)
BACKGROUND AND OBJECTIVES KSU Jaya Bersatu in Guhung Village distributes loans to independent oil palm farmers, but in the last three years, there have been stagnant bad loans to 36 debtors worth Rp574 million, even though the number of credit recipients has increased. This condition shows serious problems that risk disrupting the sustainability of cooperatives, so research needs to be conducted to examine socio-economic factors that affect the smooth payment and provide a more appropriate basis for loan policies. METHODS The study uses a descriptive quantitative approach with binary logistic regression analysis. The respondents amounted to 95 independent oil palm farmers who were selected through purposive sampling. Data were collected using questionnaires and interviews, then analyzed by the HosmerLemeshow test, Pseudo R² value, Wald test, and odds ratio. FINDINGS The results of the study showed that the value of the loan, education, number of dependents, and business experience had a significant effect on the smooth flow of credit, while income and land area had no real effect. Farmers with higher education, fewer dependents, and longer business experience tend to settle credit more smoothly. CONCLUSION Cooperatives need to be more selective in determining the amount of loans and considering the educational background and business experience of members. Financial education needs to be improved, and loan limits should be adjusted to the ability to pay to reduce the risk of bad credit.